The Impact of Consumer Buying Behavior on Customer Relationship Management in the Banking Sector - Daqar, Mohannad A. M. Abu; Smoudy, Ahmad K. A. (International Review of Management and Marketing, 2019)
The main aim of this study is to investigate the impact of Customer Relationship Management on consumer buying behavior. The researcher used primary data through a close-ended structured survey were distributed at banks customers in Palestine, and the second source of data is the interviews with selective banks top management in Palestine who is dealing with CRM. The results of this research work revealed that there is a positive strong relationship between CRM and consumer buying behavior. Consumer Buying Behavior explained 75.75% of the variance (R²= 0.7575, F (1,98) =375,703, P< 0.05). The researchers found that Consumers Buying Behavior significantly predicted CRM. Moreover, Integrated Marketing Communication tools have no significant impact on consumers buying decisions, sales promotion is the most important tool that has a consensus from the respondents that it affects their decisions. The study recommends banks to update their CRM systems to obtain the most recent data about their customers along with adopting the last cutting-edge technologies used in CRM systems to better analyzing the customers’ data. Furthermore, researches advice banks to have better views about the benefits of successful CRM systems within the same industry in order to obtain a comprehensive and precise system that could gain more benefits for customers in one hand, and on the other hand gain more profits for the banks by retaining the profitable loyal customers. Keywords: Customer Relationship Management, Consumer Buying Behavior, Integrated Marketing Communication. JEL Classifications: M30, M31, G21 DOI: https://doi.org/10.32479/irmm.8151